2008
DOI: 10.1007/s12274-008-8004-9
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of covalent sidewall functionalization of single wall carbon nanotubes by NMR spectroscopy: Side chain length dependence on the observation of the sidewall sp3 carbons

Abstract: Carboxylic acid-functionalized single walled carbon nanotubes (SWNTs) prepared via the reaction of an amino acid, NH 2 (CH 2 ) n CO 2 H where n = 1 (glycine, GLY), 5 (6-aminohexanoic acid, AHA), 10 (11-aminoundecanoic acid, AUDA), with fl uorinated single walled carbon nanotubes (F-SWNTs) have been characterized by MAS 13 C NMR spectroscopy. The ease of observing the aliphatic CH 2 groups and the resolution of the signal are dependent on the length of the amino acid's aliphatic chain. We have proposed that whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 69 publications
(44 reference statements)
1
32
2
Order By: Relevance
“…[18] Proof of covalent attachment of amine functions to fluorinated SWNTs has also been given previously. [21] In our current study, the same approach was initially taken with MWNTs (see Section 2).…”
Section: Pei-mwntmentioning
confidence: 99%
“…[18] Proof of covalent attachment of amine functions to fluorinated SWNTs has also been given previously. [21] In our current study, the same approach was initially taken with MWNTs (see Section 2).…”
Section: Pei-mwntmentioning
confidence: 99%
“…Despite its obvious importance, the ability to characterize the types and quantities of functional groups attached to SWCNT has proven to be a difficult task. A number of methods have been applied to try to estimate the degree of functionalization of a carbon nanotube (CNT) sample, including titration [6] and deoxygenation [7]r e a ctions, NMR [8], XPS [9,10] and fluorescence spectroscopy [11], as well as AFM, STM [12], and STEM imaging techniques [13]. Though each of these techniques has shown some capability at estimating the quantity of sidewall functional groups, they also have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…However, as seen in Table 1, there is no apparent relationship with regard to 31 P chemical shifts of SWNT-phosphine derivatives [16]. We have previously shown that 13 C NMR signals for substituted SWNTs are also difficult to assign in comparison with traditional organic analogs [21,22]. Thus, it is not possible to make peak assignments by direct analogy with small molecular phosphines.…”
Section: Discussionmentioning
confidence: 99%